2020
DOI: 10.1002/mds.28391
|View full text |Cite
|
Sign up to set email alerts
|

Proenkephalin Decreases in Cerebrospinal Fluid with Symptom Progression of Huntington's Disease

Abstract: Objective Identifying molecular changes that contribute to the onset and progression of Huntington's disease (HD) is of importance for the development and evaluation of potential therapies. Methods We conducted an unbiased mass‐spectrometry proteomic analysis on the cerebrospinal fluid of 12 manifest HD patients (ManHD), 13 pre‐manifest (preHD), and 38 controls. A biologically plausible and significant possible biomarker was validated in samples from a separate cohort of patients and controls consisting of 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
(47 reference statements)
3
15
1
Order By: Relevance
“…However, apart from sCJD patients, decreased or a trend towards decreased CSF PENK levels were also previously reported in HD, AD, FTD and DLB, suggesting a common pathogenetic pathway in most proteinopathies [8,10]. Further study on larger patient cohorts will be needed to fully elucidate the precise role of brain opioid peptides in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, apart from sCJD patients, decreased or a trend towards decreased CSF PENK levels were also previously reported in HD, AD, FTD and DLB, suggesting a common pathogenetic pathway in most proteinopathies [8,10]. Further study on larger patient cohorts will be needed to fully elucidate the precise role of brain opioid peptides in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 77%
“…Endogenous opioids are a group of peptides that act on opioids receptors and that derive from proteolytic cleavage of three main precursors: proenkephalin (PENK), prodynorphin (PDYN) and pro-opiomelanocortin [7]. Altered levels of CSF PDYN and/or PENK-derived peptides have been reported in Alzheimer's disease (AD), frontotemporal dementia (FTD), dementia with Lewy bodies (DLB) and Huntington's disease (HD) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…APP is a transmembrane protein with multiple physiological functions, including regulating brain iron homeostasis [53], and it is cleaved by beta- and gamma-secretase to form Aβ peptides [54, 55]. Our previous finding of decreased CSF transthyretin in HD patients [56] has also been reported in AD, where it possibly contributes to the failure of cerebral amyloid clearance [57]. This might allude to similarly decreased Aβ42 levels in HD, as noted in several other neurodegenerative disorders, most notably in AD [2429].…”
Section: Discussionmentioning
confidence: 99%
“…A 2011 study by Chen and colleagues showed increased levels of prothrombin, apolipoprotein A-IV (APOA4), and haptoglobin in CSF from a small group of control versus HD patients ( Table 3 ) [ 61 ]. Recently, a study using a larger cohort of patients reported changes in proenkephalin (PENK) and transthyretin between manifest and premanifest HD carriers which was confirmed in a second cohort, as well as numerous proteins changed between controls and HD carriers [ 62 ]. Interestingly, all three studies found increased APOA4 ( Table 3 ).…”
Section: Protein Changes In Human Postmortem Brain Csf and Hd Models Determined By Mass Spectrometry: Hd Proteomementioning
confidence: 99%